The pharmacokinetics of mycophenolate mofetil in Thai kidney transplant recipients - S. Jirasiritham (2018)
Mycophenolate mofetil, in addition to cyclosporine and prednisolone significantly reduces the rate of acute rejection. The original recommended dose of MMF is fixed at 2 g/day. However, Thai patients cannot tolerate this dose due to gastrointestinal adverse effects. So the majority of patients are maintained on MMF at doses ranging from 0.5 to 2 g/day, according to their tolerability with an acceptable rate of acute rejection episodes. This study sought to determine the steady state pharmacokinetics of MMF in Thai kidney transplant recipients on stable doses of MMF. Forty-six kidney transplant patients more than 3 months on a stable MMF dose of 0.5, 1, 1.5, and 2 g/day together with cyclosporine and prednisolone underwent a single pharmacokinetic blood sampling for 12 hours following the morning dose of MMF. The analysis of plasma concentrations of mycophenolic acid (MPA), the sole pharmacologically active metabolite of MMF, was performed by using an high performance liquid chromatography method. Sparse efficient sampling strategies were employed to optimize the blood sampling schedule. Hence, blood samples were collected at 0, 0.5, 2, 12 hours after the MMF dose. The sampling time was designed to best estimate AUC0-tauat steady state. The initial MPA-Bayesian estimator were used for MPA concentrations that would allow the best estimation of Vc, CLt, and Ka. In this study, there is a high interindividual variability in the AUC. The median MPA AUC was 34.3 ug.h/mL (range 14.1-65.4). Thirty-one of 45 (68.9%) patients had a MPA AUC within 20 to 40 ug.h/mL, which is the most reasonable risk: benefit ratio in terms of preventing acute rejection episodes. Forty-one of 45 (91.1%) patients had MPA AUC within 20 to 60 ug.h/mL, which is the MPA therapeutic range. The highest Pearson correlation coefficient of determination between MPA AUC and a single concentration was observed with MPA 2 hours (r = 0.622) Without a fixed dosing regimen, most Thai kidney transplant recipients who receive MMF as part of a maintenance immunosuppressive regimen have the MPA AUC within the therapeutic window. The single drug concentration that correlates well with the AUC is MPA at 2 hours postdose.